DISCOURSE ANALYSIS OF THE COLOR TERM “QÍZÍL” (RED) IN THE KARAKALPAK EPIC QÍRQ QÍZ” (FORTY GIRLS): DISCOURSE ANALYSIS OF THE COLOR TERM “QÍZÍL” (RED) IN THE KARAKALPAK EPIC QÍRQ QÍZ” (FORTY GIRLS) - Ametova, Arzigul (Журнал иностранных языков и лингвистики, 2025)
In fact, color symbolism in epic literature serves as a vital semiotic resource for expressing collective worldviews, emotions, and values. In the Karakalpak epic Qırq Qız, the color "qızıl" (red) plays a multilayered role. It is associated not only with physical descriptions but also with symbolic meanings such as courage, bloodshed, youth, honor, and divine beauty. This study explores the discursive patterns and functions of "qızıl" (red) within the narrative structure of the epic, using methods from cognitive linguistics, cultural linguistics, and discourse analysis